Faktor Risiko Kurang Energi Kronis (KEK) pada Ibu Hamil di Cikembar Kabupaten Sukabumi - Muh Guntur Sunarjono Putra; Mira Dewi (ARTERI : Jurnal Ilmu Kesehatan, 2020)
One of the nutritional problems in Indonesia is Chronic Energy Deficiency (CED) among pregnant women, which is the cause of the high maternal mortality rate and low birth weight. This study aims to analyze the risk factors of CED in pregnant women with cross-sectional study design. The subject in this research were 70 pregnant women with and without CED (normal) at Cikembar Health Center Sukabumi district. CED group had less nutrition and health knowledge in comparison to the normal group. The level of energy and protein sufficiency in both groups was generally in the deficit category. Most of the CED group food security was in food insecurity while the normal group was in food vulnerable conditions. Based on the results of logistic regression analysis, it shows that there is a significant relationship between maternal knowledge and household food security with the incidence of CED in pregnant women (p <0.05), but between the level of energy and protein adequacy shows an insignificant relationship (p> 0.05). The multiple logistic regression analysis results indicate that the factor affecting the incidence of CED in pregnant women is household food security. Besides, the level of knowledge of nutrition and health, food consumption, and household food security in CED pregnant women is low or deficit compared to the normal pregnant women.